Potentially inappropriate medications use among the older patients diagnosed with psychiatric diseases in Saudi Arabia: a cross-sectional study - Alsultan, Mohammed M.; Alhawas, Solaiman M.; Alhajri, Leena H.; Alamer, Khalid A.; Alahmari, Abdullah K.; AlQarni, Amani M.; Al-Awad, Feras A. (Frontiers in Medicine, 2025)
ObjectiveTo examine the prevalence of potentially inappropriate medications (PIMs) prescribed among older patients diagnosed with psychiatric diseases and to identify associated factors.MethodsThis cross-sectional study was conducted among older patients who visited outpatient clinics in Saudi Arabia between June 1st, 2019, and May 31st, 2023. PIMs use was estimated using the updated 2019 American Geriatric Society (AGS) Beers criteria. Data were analyzed using chi-square or Fisher's exact test for categorical variables and t-test for continuous variables to compare patients with and without PIMs. In addition, the Pearson correlation test was performed between the total number of prescriptions and the number of PIMs. Multivariable logistic regression analysis was used to explore PIMs. Statistical significance was set at p < 0.05.ResultsOur study included 306 patients with psychiatric diseases, with 156 (50.98%) in the PIMs group and 150 (49.02%) in the non-PIMs group. There was a considerable positive correlation between the total number of prescriptions and the number of PIMs (r = 0.76; p < 0.0001). The adjusted logistic regression analysis revealed a significantly higher risk of PIMs use in individuals with psychiatric diseases and comorbid neurological diseases compared to those without [adjusted odds ratio (AOR) = 2.48, 95% CI [1.15–5.32]]. In contrast, the risk of PIMs use was not significantly greater for older individuals with psychiatric diseases and comorbid hypertension {AOR = 1.67, 95% CI [(0.79–3.54)]}, diabetes mellitus {AOR = 1.25, 95% CI [(0.66–2.34)]}, or pulmonary disease {AOR = 2.34, 95% CI [(0.69–7.96)]}.ConclusionThis study highlighted the elevated number of PIMs in older adults with psychiatric diseases in the outpatient setting, particularly those with comorbid neurological diseases. Therefore, clinical pharmacists may play a crucial role in improving the outcomes of patients diagnosed with psychiatric illnesses. Finally, future studies should examine additional strategies to reduce the use of PIMs in this population.